Mathematical modeling based on mixing problems, - Nur Farahim Arzmi, 1990-; Khairil Anuar Arshad, supervisor; Fakulti Sains (2012)
Project Paper (Sarjana Muda Sains (Matematik Industri)) - Universiti Teknologi Malaysia, 2012